The first Paul : reclaiming the radical visionary behind the Church's conservative icon - Borg, Marcus J.; Crossan, John Dominic ([New York] : HarperOne, 2009)
The authors show how the apostle was slowly but steadily "deradicalized" to fit Roman social norms in regards to slavery, patriarchy, and patronage. In truth, Paul was an appealing apostle of Jesus whose vision of life "in Christ"--one of his favored phrases--is remarkably faithful to the message of Jesus himself.
Paul : appealing or appalling? -- How to read a Pauline letter -- The life of a long-distance apostle -- "Jesus Christ is Lord" -- "Christ crucified" -- "Justification by grace through faith" -- Life together "in Christ" -- The death of an apostle.
Includes bibliographical references (p. [225]) and index.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; Bible. -- Theology